Non-formal learning practices among students in Kazakhstan: Perceptions, challenges, and opportunities - Kulgildinova, Tulebike; Sarsembayeva, Araily; Surova, Darya; Ayapbergenova, Gulsum; Nurgaliyeva, Saniya (International Journal of Innovative Research and Scientific Studies, 2025)
Kazakhstani university practices benefit from the adaptability and mobility of non-formal education in the face of continuous changes in the global educational landscape. The potential of non-formal education offers opportunities to improve students' professional and universal competencies in a variety of training formats. The study aims to investigate students' perceptions, engagement, and challenges regarding non-formal learning. The study involved 422 students from D. Serikbayev East Kazakhstan Technical University. There were two phases of the research methodology. The first section was carried out as a theoretical study. The second phase comprised a quantitatively based field study. Questionnaire surveys are the field research method. The findings demonstrate that there are trends in the growth of non-formal education, as well as the paradoxes and both explicit and latent functions. The relationship between their academic achievement and skill development and non-formal learning techniques in students is critical. The study's findings show that students' academic performance and skill development are enhanced by non-formal learning. The findings are consistent with the article's research objectives. From a practical perspective, universities can use these findings to develop strategies that facilitate informal learning. Institutions can create a learning environment that encourages lifelong knowledge acquisition by incorporating online learning resources, supporting time management skills, and stimulating intrinsic motivation.